Protein profile of Dabry's sturgeon (Acipenser dabryanus) spermatozoa and relationship to sperm quality - Li, Ping; Du, Hao; Qiao, Xin Mei; Liu, Zhi Gang; Zhou, Qiong; Wei Wei, Qi (Animal reproduction science, 2019)
Knowledge of conditions affecting sperm quality is essential for efficient culture of fish for commercial purposes and conservation of species. Two-dimensional gel electrophoresis and matrix-assisted laser desorption/ionization time of flight mass spectrometry were used to characterize the proteomic profile of Acipenser dabryanus spermatozoa relative to motility and fertilization capacity. There were differential amounts of protein in 313 spots in spermatozoa of males classified to have relatively greater or lesser spermatozoa quality. The functions of 43 of 50 selected proteins were identified. The proteins in 14 spots were involved in metabolism, and of these, proteins in 11 spots were highly abundant in spermatozoa of males categorized to have spermatozoa of greater quality, including pyruvate kinase, enolase B, phosphoglycerate kinase, lactate dehydrogenase, cytosolic malate dehydrogenase, brain creatine kinase b, Ckmb protein, and nucleoside diphosphate kinase. The proteins involved in mechanics of flagellum movement were identified, including the dynein intermediate chain, radial spoke head 1 homolog; ropporin-1-like, Bardet-Biedl syndrome 5, ADP-ribosylation factor-like protein 3, tektin-4, gamma-actin, and tubulin cytoskeleton proteins to be differentially abundant in spermatozoa that were classified relatively greater or lesser quality. Heat shock proteins, copper/zinc superoxide dismutase and peroxiredoxins, which are involved in stress response were of differential abundance in spermatozoa from males with spermatozoa in the two different classification groups. Proteins were also detected that are involved in protein folding and binding, or hydrolase activity. The results are valuable for the prediction of sperm quality and for reproduction management in A. dabryanus and other threatened species.
Keywords: Spermatozoa; Animals; rybí proteiny; Proteomics; Sperm Motility; mužské pohlaví; zvířata; proteomika; Fishes; Male; spermie; motilita spermií; Fish Proteins; ryby